Nellore cloned calf viability during the postnatal period - Santos, Guilherme Gonçalves Fabretti; Cholfe, Bruno Fornitano; Paiola, Igor Augusto Andreta; Morelli Júnior, João; Birgel Junior, Eduardo Harry; Mendes, Luiz Cláudio Nogueira [UNESP]; Luvizotto, Maria Cecília Rui [UNESP]; Feitosa, Francisco Leydson Formiga [UNESP] (FapUNIFESP (SciELO), 2021)
This study evaluated the viability of Nellore cloned calves derived from somatic cell nuclear transfer (SCNT) and compare their viability with animals of the same breed derived from in vitro fertilization (IVF). Thus, two groups were formed. Group I (GI) consisted of 10 calves derived from SCNT and group II (GII) consisted of 10 calves derived from IVF. The differences detected between the groups were in the physical examination of the respiratory tract in GI, which represented the most common clinical-pathological disturbances. The Apgar index score indicated that 80% of GI animals were depressed and all had pale mucous membranes. Thus, anemia was reported in GI. In GII, this started at 12 h of life and was probably caused by an iron deficiency. Moreover, total calcium and ionized calcium levels were higher in GI immediately after birth. These alterations probably resulted in a high incidence of mortality in GI, reaching 90% of the calves, whereas mortality was only 20% for the calves in GII. In conclusion, cloned calves, which were derived from SCNT, had physiological and metabolic alterations after delivery, leading to a higher mortality rate during the perinatal period.
Viabilidade de bezerros nelores clonados durante o período pós natal imediato
Keywords: Calves; Clinical; Cloned; Laboratorial assessment; Pathology